2018
DOI: 10.1039/c8sc03672a
|View full text |Cite
|
Sign up to set email alerts
|

Cs3VO(O2)2CO3: an exceptionally thermostable carbonatoperoxovanadate with an extremely large second-harmonic generation response

Abstract: A highly thermostable carbonatoperoxovanadate, Cs3VO(O2)2CO3, exhibits a remarkably strong SHG response of approximately 23.0 times that of KDP, which is the largest among those of the reported NLO carbonate materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 134 publications
(79 citation statements)
references
References 58 publications
2
77
0
Order By: Relevance
“…[18] By doing so,quite afew candidates for UV/DUV NLO materials have been discovered. [19] Meanwhile,an umber of recently reported crystals with outstanding properties such as Pb 2 BO 3 Cl, [20] Cs 3 VO-(O 2 ) 2 CO 3 , [21] Bi 3 Te BO 9 , [22] APbCO 3 F( A = Rb,C s), [23] and BiFSeO 3 [24] should be good candidates as visible/near-IR NLO materials.Incontrast, in the mid-IR region (2.0-20 mm), af ew NLO materials such as AgGaS 2 , [25] AgGaSe 2 , [25] and ZnGeP 2 [26] are commercially available to date.However,they all suffer from some demerits such as low LDT and difficulty in crystal growth. Therefore,wide applications of the present materials have been severely hindered.…”
Section: Introductionmentioning
confidence: 99%
“…[18] By doing so,quite afew candidates for UV/DUV NLO materials have been discovered. [19] Meanwhile,an umber of recently reported crystals with outstanding properties such as Pb 2 BO 3 Cl, [20] Cs 3 VO-(O 2 ) 2 CO 3 , [21] Bi 3 Te BO 9 , [22] APbCO 3 F( A = Rb,C s), [23] and BiFSeO 3 [24] should be good candidates as visible/near-IR NLO materials.Incontrast, in the mid-IR region (2.0-20 mm), af ew NLO materials such as AgGaS 2 , [25] AgGaSe 2 , [25] and ZnGeP 2 [26] are commercially available to date.However,they all suffer from some demerits such as low LDT and difficulty in crystal growth. Therefore,wide applications of the present materials have been severely hindered.…”
Section: Introductionmentioning
confidence: 99%
“…To nd a KBBF replacement, many new NLO crystals have been developed continuously, but have so far been unable to achieve desired NLO properties. [7][8][9][10] Recently, it was shown that uorooxoborates and uorophosphates with mixed O/F anionic groups might be recognized as new sources for discovering DUV NLO materials. For example, Pan's group proposed that the [BO x F 4Àx ] (x ¼ 1, 2, 3) tetrahedra are good units to balance the multiple criteria of DUV NLO materials.…”
mentioning
confidence: 99%
“…This measured birefringence is larger than the majority of oxides, such as the commercially used birefringent crystals CaCO 3 (0.16 at 800 nm) and α‐BaB 2 O 4 (0.122 at 532 nm), the peroxides Cs 3 VO(O 2 ) 2 CO 3 (calc. 0.105 at 1064 nm) and Rb 3 VO(O 2 ) 2 CO 3 (calc. 0.075 at 1064 nm), as well as the recently reported Li 2 Na 2 B 2 O 5 (0.095 at 532 nm), Ca(BO 2 ) 2 (0.1355 at 546 nm), Sn 2 B 5 O 9 Cl (0.168 at 546 nm), NaCa 4 V 5 O 17 (calc.…”
Section: Figurementioning
confidence: 99%